2009
DOI: 10.1002/ejoc.200901099
|View full text |Cite
|
Sign up to set email alerts
|

Amino–Acetone‐Bridged Cyclodextrins ― Artificial Alcohol Oxidases

Abstract: A new series of α-and β-cyclodextrin derivatives containing a substituted amino-acetone bridge attached to the 6A and 6D positions of the cyclodextrin are reported. The synthesis starts from the known α-or β-cyclodextrin A,D-diols, which were either oxidized to α-or β-cyclodextrin A,D-dicarbaldehydes and then coupled with 1,3-diamino-2-propanol by a reductive amination reaction and further modified to give the final 6A ,6 D -diamino-6 A ,6 D -dideoxy-N,NЈ-(2-oxopropa-1,3-dienyl)-N,NЈ-acetyl-α-or -β-cyclodextri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 57 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Marinescu et al reported the synthesis of new αand β-cyclodextrin derivatives with good enzyme-like activity in the oxidation of alcohols with H 2 O 2 [66]. In this context, different cyclodextrin derivatives (Figure 2, left) have also been described to catalyse the oxidation of anilines to nitroarenes [67].…”
Section: Oxidation With Hydrogen Peroxidementioning
confidence: 99%
“…Marinescu et al reported the synthesis of new αand β-cyclodextrin derivatives with good enzyme-like activity in the oxidation of alcohols with H 2 O 2 [66]. In this context, different cyclodextrin derivatives (Figure 2, left) have also been described to catalyse the oxidation of anilines to nitroarenes [67].…”
Section: Oxidation With Hydrogen Peroxidementioning
confidence: 99%
“…Cyclodextrins are cyclic oligosaccharides of at least six α-1-4-linked α-Dglucopyranoside units, with a peculiar internal toroidal shape with a cavity able to recognize and host several molecules. In the past, CDs had already been used to build enzyme models [175], and Li-Wu et al used this strategy to study Se-and Te-based artificial enzymes, highlighting a higher efficiency of Te-based CDs in catalyzing the model reaction (NADPH), especially when the chalcogens are inserted in the 2-position rather than in the 6position. Moreover, the activity of dual-bridged enzymatic mimics was found to be higher than that of single-bridged ones.…”
Section: Other Classes Of Diselenides: Towards Macromolecular Gpx Mimicsmentioning
confidence: 99%